Uso de subproductos de cacao en la alimentación de cuyes (Cavia porcellus). - Maliza Orozco, Freddy Fernando (2010)
During the process of Ambato traditional chocolate’s elaboration, we get a by product, this is husk at cacao, additional element which has a big impact in this zones environment, whose correct use presents a good idea to feed same farm animals, specially guinea pig. Next investigation took place in the province Tungurahua, Pelileo, Benitez, in a farm that belongs to Maliza Torres’ Family. This farmville is in Carmen sector by the road Ambato – Baños. The duration of this field investigation last 60 days. The objective of this investigation was to evaluate the consumption of rations which including of cacao husk, to measure the going of weight in guinea pig, the average consumption, to establish the nutritional conversion , and the yield to the find channel. For these was necessary to take just 48guinea pig to wich we provisioned them rations as 10%, 20%, and 30% of including of cacao husk. The results demonstrated that better averages about the aliments’ consumption and to GMD of weight was obtained with the witness treatment ( 0% cacao husk), with price as 32,25 g and 9,46g respectively . In the same farm below the index of conversion parameters and the yield to the final channel best results was gotten with the witness treatment , with the values of 3,44 and 66,25% rendition of the channel. In the economic analysis the T2 treatment present the best index with 0,35 at promedium.